SIP-based proactive and adaptive mobility management framework for heterogeneous networks - YEE, Y; CHOONG, K; LOW, A; TAN, S (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2008)
In this paper, we present and evaluate the performance of a mobility management system called the Proactive and Adaptive Handover (PAHO) system. PAHO is an application-level approach that uses SIP to manage client-initiated connection handoff across heterogeneous networks based on the IEEE 802.21 framework with designated user/configuration policy. Unlike conventional systems which make sub-optimal decision when managing connection handoff due to limited awareness of the relevant context for the application/service being delivered, PAHO defines proper interface to interact with the application as to determine when and to where the handoff and/or codec switching should take place in the event of network performance degradation. The results showed that using the PAHO approach on an audio/video conferencing session helps reducing the overall handover delay from 10.766s (on non-PAHO system) down to at least 288ms, and slowing down the degradation of MOS value throughout the entire experiment in the event of signal degradation as well as network congestion. It is also shown that load balancing among the access points (AP) could be achieved with an improved Information Server (IS). (C) 2007 Elsevier Ltd. All rights reserved.